Interview with Vanessa de Oliveira Andreotti: Learning to see in the dark: Grief, hope, and the end of enlightenment fantasies - van Voorst, Roanne (Futures Reframed, 2026)
This summer I read Vanessa de Oliveira Andreotti’s book ‘Hospicing Modernity’ among fragrant lavender, in a wild French garden. I was on holiday: the academy, and even politics and wars, seemed far away for a moment. Thankfully so, because like so many people around me I needed this pause to find some mental rest, to regain a bit of courage after all the disheartening news that I’d seen on the news, even to recover some hope. Or so I thought. Until I opened this book and began to realise that hope - at least a naïve version of it - is the very last thing we need to imagine that other futures might still be possible.